Level of education in fishermen community is a low classified, one of something is because of the poverty in the fisherman community. In other, fishermen perception about formal education will influential to the level of education in fishermen community. This research have a direction to know the fishermen perception level about formal education, to know the factors that influence it, to know the relation between that perception with the fishermen behavior to sent their children to school, and t - Ninik Sriyanti; Istiqlaliyah Muflikhati; Anna Fatchiya (Buletin Ekonomi Perikanan, 2006)
Level of education in fishermen community is a low classified, one of something is because of the poverty in the fisherman community. In other, fishermen perception about formal education will influential to the level of education in fishermen community. This research have a direction to know the fishermen perception level about formal education, to know the factors that influence it, to know the relation between that perception with the fishermen behavior to sent their children to school, and to know how much percentage of cost that their spent to their children education. This research used the cased study method, and analyzed descriptively. The result of the research showed that almost of fishermen in the Rembang District, Rembang Regency, Central Java Province have a high perception level about formal education. The factors that influence it such as age level in the present, the children value for the future, their hope for'their children jobs, community value, and the policy of the local governmant in Rembang Regency about education. The relation between fishermen perception about formal education with the fishermen behavior to sent their children to school have real and positive characters. The cost of the education that spent by fishermen family to their children have an average value. That average value is about 18.25 % from the total of their total spending.